Advancing Health Equity for Native American Youth: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
More than 2 million Americans below age 24 self-identify as being of American Indian or Alaska Native descent. Many of the serious behavioral, emotional, and physical health concerns facing young people today are especially prevalent with Native youth (e.g., depression, violence, and substance abuse). Adolescent Native Americans have death rates two to five times the rate of whites in the same age group because of higher levels of suicide and a variety of risky behaviors (e.g., drug and alcohol use, inconsistent school attendance). Violence, including intentional injuries, homicide, and suicide, accounts for three-quarters of deaths for Native American youth ages 12 to 20. Suicide is the second leading cause of death2014and 2.5 times the national rate2014for Native youth ages 15 to 24. Arrayed against these health problems are vital cultural strengths on which Native Americans can draw. At a workshop held in 2012, by the National Academies of Sciences, Engineering, and Medicine, presenters described many of these strengths, including community traditions and beliefs, social support networks, close-knit families, and individual resilience. In May 2014, the Academies held a follow-up workshop titled Advancing Health Equity for Native American Youth. Participants discussed issues related to (1) the visibility of racial and ethnic disparities in health and health care as a national problem, (2) the development of programs and strategies by and for Native and Indigenous communities to reduce disparities and build resilience, and (3) the emergence of supporting Native expertise and leadership. This report summarizes the presentations and discussions from the workshop.

Lesbian Health: Current Assessment and Directions for the Future - Institute of Medicine (The National Academies Press, 1999)
Women's health, as a field of study, is a developing discipline. Health theories in general have been based on studies of men. However, in recent years, more attention has shifted to women's health, realizing the disparities between men and women in relation to their health. During the last two decades, a similar shift has occurred for a group of women2014lesbian women2014to further identify and specify their health needs. Over the past decade, lesbians have organized to call for attention to the health issues of this community, resulting in several federally funded research initiatives. This book offers a comprehensive view of what is known about lesbian health needs and what questions need further investigation, including: How do we define who is lesbian? Are there unique health issues for lesbians? Are lesbians at higher or lower risk for such health problems as AIDS, sexually transmitted diseases, breast cancer, mental disorders, and substance abuse? How does homophobia affect lesbian health and the funding of research on lesbian health? How do lesbian health needs fit into the health care system and the larger society? What risk and protective factors shape the physical and mental health of lesbians? The book discusses how to determine which questions to ask about sexual orientation, the need to obtain information without violating privacy, the importance of considering racial and ethnic diversity in the study of lesbians, strategies for exchanging information among researchers and disseminating findings to the public, and mechanisms for supporting greater numbers of researchers. Lesbian Health takes a frank look at the political pressures, community attitudes, and professional concerns uniquely affecting the study of lesbian health issues. The book explores many other issues including the potential for transferring findings in this field to other population groups, including other rare populations and women in general.

Speaking of Health: Assessing Health Communication Strategies for Diverse Populations - Institute of Medicine (The National Academies Press, 2002)
We are what we eat. That old expression seems particularly poignant every time we have our blood drawn for a routine physical to check our cholesterol levels. And, it's not just what we eat that affects our health. Whole ranges of behaviors ultimately make a difference in how we feel and how we maintain our health. Lifestyle choices have enormous impact on our health and well being. But, how do we communicate the language of good health so that it is uniformly received-and accepted-by people from different cultures and backgrounds? Take, for example, the case of a 66 year old Latina. She has been told by her doctor that she should have a mammogram. But her sense of fatalism tells her that it is better not to know if anything is wrong. To know that something is wrong will cause her distress and this may well lead to even more health problems. Before she leaves her doctor's office she has decided not to have a mammogram-that is until her doctor points out that having a mammogram is a way to take care of herself so that she can continue to take care of her family. In this way, the decision to have a mammogram feels like a positive step. Public health communicators and health professionals face dilemmas like this every day. Speaking of Health looks at the challenges of delivering important messages to different audiences. Using case studies in the areas of diabetes, mammography, and mass communication campaigns, it examines the ways in which messages must be adapted to the unique informational needs of their audiences if they are to have any real impact. Speaking of Health looks at basic theories of communication and behavior change and focuses on where they apply and where they don't. By suggesting creative strategies and guidelines for speaking to diverse audiences now and in the future, the Institute of Medicine seeks to take health communication into the 21st century. In an age where we are inundated by multiple messages every day, this book will be a critical tool for all who are interested in communicating with diverse communities about health issues.

Health and Behavior: The Interplay of Biological, Behavioral, and Societal Influences - Institute of Medicine (The National Academies Press, 2001)
Health and Behavior reviews our improved understanding of the complex interplay among biological, psychological, and social influences and explores findings suggested by recent research2014including interventions at multiple levels that we can employ to improve human health. The book covers three main areas: What do biological, behavioral, and social sciences contribute to our understanding of health2014including cardiovascular, immune system and brain functioning, behaviors that influence health, the role of social networks and socioeconomic status, and more. What can we learn from applied research on interventions to improve the health of individuals, families, communities, organizations, and larger populations? How can we expeditiously translate research findings into application?

A Health Equity Approach to Obesity Efforts: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On April 1, 2019, the National Academies of Sciences, Engineering, and Medicine held a public workshop, A Health Equity Approach to Obesity Efforts, in Washington, DC. The workshop explored the history of health equity issues in demographic groups that have above-average obesity risk, and considered principles and approaches to address these issues as part of obesity prevention and treatment efforts. Speaker presentations addressed three areas: current policies and practices that either perpetuate health inequities or advance health equity; mechanisms to support community-driven solutions that can influence the social determinants of health; and approaches for fostering multisector collaboration to address disparities by exploring the issues related to the creation, implementation, and evaluation of equity-oriented programs, policies, and systems changes. Participants also discussed research needs to inform and mobilize equity-centered obesity prevention and treatment actions. This publication briefly summarizes the presentations and discussions from the workshop.

Framing the Dialogue on Race and Ethnicity to Advance Health Equity: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
In February 2016, the National Academies of Sciences, Engineering, and Medicine held a workshop in which speakers shared strategies for individuals, organizations, and communities to advance racial and health equity. Participants discussed increasing awareness about the role of historical contexts and dominant narratives in interpreting data and information about different racial and ethnic groups, framing messages for different social and political outcomes, and readying people to institutionalize practices, policies, and partnerships that advance racial and health equity. This publication serves as a factual summary of the presentations and discussions from the workshop.

Framework for Equitable Allocation of COVID-19 Vaccine - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
In response to the coronavirus disease 2019 (COVID-19) pandemic and the societal disruption it has brought, national governments and the international community have invested billions of dollars and immense amounts of human resources to develop a safe and effective vaccine in an unprecedented time frame. Vaccination against this novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), offers the possibility of significantly reducing severe morbidity and mortality and transmission when deployed alongside other public health strategies and improved therapies. Health equity is intertwined with the impact of COVID-19 and there are certain populations that are at increased risk of severe illness or death from COVID-19. In the United States and worldwide, the pandemic is having a disproportionate impact on people who are already disadvantaged by virtue of their race and ethnicity, age, health status, residence, occupation, socioeconomic condition, or other contributing factors. Framework for Equitable Allocation of COVID-19 Vaccine offers an overarching framework for vaccine allocation to assist policy makers in the domestic and global health communities. Built on widely accepted foundational principles and recognizing the distinctive characteristics of COVID-19, this report's recommendations address the commitments needed to implement equitable allocation policies for COVID-19 vaccine.

The Impact of Juvenile Justice System Involvement on the Health and Well-Being of Youth, Families, and Communities of Color: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Involvement with the juvenile justice system can impact young people's physical and mental health and well-being throughout their lives, as well as the health and well-being of their families and communities. Youth of color are more likely to become involved with the juvenile justice system, and suffer worse outcomes in sentencing, during incarceration, and after release. The National Academies of Sciences, Engineering, and Medicine's Roundtable on the Promotion of Health Equity convened a workshop to discuss the impact that juvenile justice system involvement has on the health and well-being of adolescents, families, and communities of color; examine policies that are successful in improving outcomes; and explore what needs to be done to improve all aspects of encounters with the juvenile justice system. The workshop suggested pursuing alternatives to traditional juvenile justice systems that would allow adolescents to stay in their communities rather than in detention, responding to behavioral problems in youth with interventions that promote health and positive development rather than punishment, and tailoring interventions and programming to participants' cultural background and gender identity. This report summarizes the proceedings of the workshop.

A Health Equity Approach to Obesity Efforts: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The obesity crisis in the United States disproportionately affects some demographic groups more than others. Contextual influences on obesity are complex and include an individual's weight-related behaviors and outcomes, the intermediate variables that influence these behaviors and outcomes, and broader, upstream historical, social, economic, physical, and policy contexts. The National Academies convened a workshop on April 1, 2019 to explore the history of health equity issues in demographic groups that have above-average obesity risk and to consider principles and approaches to address these issues as part of obesity prevention and treatment efforts. This publication summarizes the presentations and discussions from the workshop.

Bringing Public Health into Urban Revitalization: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
A particularly valuable opportunity to improve public health arises when an urban area is being redesigned and rebuilt following some type of serious disruption, whether it is caused by a sudden physical event, such as a hurricane or earthquake, or steady economic and social decline that may have occurred over decades. On November 10, 2014, the Institute of Medicine's Roundtable on Environmental Health Sciences, Research, and Medicine held a workshop concerning the ways in which the urban environment, conceived broadly from factors such as air quality and walkability to factors such as access to fresh foods and social support systems, can affect health. Participants explored the various opportunities to reimagine the built environment in a city and to increase the role of health promotion and protection during the process of urban revitalization. Bringing Public Health into Urban Revitalization summarizes the presentations and discussions from this workshop.

Pharmacokinetics and Drug Interactions in the Elderly and Special Issues in Elderly African-American Populations: Workshop Summary - Institute of Medicine (The National Academies Press, 1997)
Reports in the popular press about the increasing longevity of Americans and the aging of the baby boom generation are constant reminders that the American population is becoming older. Consequently, an issue of growing medical, health policy, and social concern is the appropriate and rational use of medications by the elderly. Although becoming older does not necessarily correlate with increasing illness, aging is associated with anatomical and physiological changes that affect how medications are metabolized by the body. Furthermore, aging is often related to an increased frequency of chronic illness (often combined with multiple health problems) and an increased use of medications. Thus, a better understanding of the absorption, distribution, metabolism, and excretion of drugs; of the physiologic responses to those medications; as well as of the interactions among multiple medications is crucial for improving the health of older people.

Guidance for the National Healthcare Disparities Report - Institute of Medicine (The National Academies Press, 2002)
The Agency for Healthcare Research Quality commissioned the Institute of Medicine establish a committee to provide guidance on the National Healthcare Disparities Report is of access to health care, utilization of services, and the services received. The committee was asked to con population characteristics as race and ethnicity, society status, and geographic location. It was also asked to examine factors that included possible data sources and types of measures for the report.

Promoting Health: Intervention Strategies from Social and Behavioral Research - Institute of Medicine (The National Academies Press, 2000)
At the dawn of the twenty-first century, Americans enjoyed better overall health than at any other time in the nation's history. Rapid advancements in medical technologies, breakthroughs in understanding the genetic underpinnings of health and ill health, improvements in the effectiveness and variety of pharmaceuticals, and other developments in biomedical research have helped develop cures for many illnesses and improve the lives of those with chronic diseases. By itself, however, biomedical research cannot address the most significant challenges to improving public health. Approximately half of all causes of mortality in the United States are linked to social and behavioral factors such as smoking, diet, alcohol use, sedentary lifestyle, and accidents. Yet less than five percent of the money spent annually on U.S. health care is devoted to reducing the risks of these preventable conditions. Behavioral and social interventions offer great promise, but as yet their potential has been relatively poorly tapped. Promoting Health identifies those promising areas of social science and behavioral research that may address public health needs. It includes 12 papers2014commissioned from some of the nation's leading experts2014that review these issues in detail, and serves to assess whether the knowledge base of social and behavioral interventions has been useful, or could be useful, in the development of broader public health interventions.

Perspectives on Health Equity and Social Determinants of Health - National Academy of Medicine (The National Academies Press, 2017)
Social factors, signals, and biases shape the health of our nation. Racism and poverty manifest in unequal social, environmental, and economic conditions, resulting in deep-rooted health disparities that carry over from generation to generation. In Perspectives on Health Equity and Social Determinants of Health, authors call for collective action across sectors to reverse the debilitating and often lethal consequences of health inequity. This edited volume of discussion papers provides recommendations to advance the agenda to promote health equity for all. Organized by research approaches and policy implications, systems that perpetuate or ameliorate health disparities, and specific examples of ways in which health disparities manifest in communities of color, this Special Publication provides a stark look at how health and well-being are nurtured, protected, and preserved where people live, learn, work, and play. All of our nation2019s institutions have important roles to play even if they do not think of their purpose as fundamentally linked to health and well-being. The rich discussions found throughout Perspectives on Health Equity and Social Determinants of Health make way for the translation of policies and actions to improve health and health equity for all citizens of our society. The major health problems of our time cannot be solved by health care alone. They cannot be solved by public health alone. Collective action is needed, and it is needed now.

Examining the History, Consequences, and Effects of Race-Based Clinical Algorithms on Health Equity: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The National Academies Roundtable on the Promotion of Health Equity hosted a virtual public workshop in July 2023 to discuss the premise, history, and development of race-based clinical algorithms and their contributions to health inequities. Examining ways to promote race-conscious medicine, participants explored the underlying assumptions of racial differences in physiology, and parameters for identifying instances when race and ethnicity as social constructs are legitimate considerations for improving health equity, such as when promoting outreach, screening, and community education and engagement.

Collecting Sexual Orientation and Gender Identity Data in Electronic Health Records: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Collecting Sexual Orientation and Gender Identity Data in Electronic Health Records: Workshop Summary reviews the statement of task set to the committee which required them to collect sexual orientation and gender identity data in electronic health records. This report summarizes the invited presentations and facilitated discussions about current practices around sexual orientation and gender identity data collection, the challenges in collecting these data, and ways in which these challenges can be overcome. Areas of focus for the workshop include the clinical rationale behind collecting these data, standardized questions that can be used to collect these data, mechanisms for supporting providers and patients in the collection of these data, technical specifications involved in creating standards for sexual orientation and gender identity data collection and exchange, and policy considerations related to the health information technology (HIT) Meaningful Use process being overseen by the Department of Health and Human Services. This report summarizes the workshop agenda, select invited speakers and discussants, and moderate the discussions. Invited participants will include lesbian, gay, bisexual, and transgender (LGBT) health care consumer advocates, providers with experience working with LGBT populations, HIT vendors and other HIT specialists, health care administrators, and policy makers.

Race, Ethnicity, and Language Data: Standardization for Health Care Quality Improvement - Institute of Medicine (The National Academies Press, 2009)
The goal of eliminating disparities in health care in the United States remains elusive. Even as quality improves on specific measures, disparities often persist. Addressing these disparities must begin with the fundamental step of bringing the nature of the disparities and the groups at risk for those disparities to light by collecting health care quality information stratified by race, ethnicity and language data. Then attention can be focused on where interventions might be best applied, and on planning and evaluating those efforts to inform the development of policy and the application of resources. A lack of standardization of categories for race, ethnicity, and language data has been suggested as one obstacle to achieving more widespread collection and utilization of these data. Race, Ethnicity, and Language Data identifies current models for collecting and coding race, ethnicity, and language data; reviews challenges involved in obtaining these data, and makes recommendations for a nationally standardized approach for use in health care quality improvement.

Health Communication with Immigrants, Refugees, and Migrant Workers: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
In March 2017, the Roundtable on Health Literacy of the National Academies of Sciences, Engineering, and Medicine convened a workshop focused on health communication with people from immigrant, refugee, and migrant worker populations. The workshop was organized to explore the application of health literacy insights to the issues and challenges associated with addressing the health of immigrants, refugees, and migrant workers. Participants explored issues of access and services for these populations as well as outreach and action. This publication summarizes the presentations and discussions from the workshop.

Measuring Health Performance in the Public Sector: A Summary of Two Reports - National Research Council (The National Academies Press, 1999)
The Panel on Performance Measures and Data for Public Health Performance Partnership Grants was established at the request of the U.S. Department of Health and Human Services (DHHS). Its charge is to examine the state of the art in performance measurement for public health and to recommend measures that could be used to monitor the Performance Partnership Grant agreements to be negotiated between each state and the federal government. The panel was asked to consider performance measures in ten areas, which are clearly a subset of the full range of traditional public health concerns: chronic diseases; sexually transmitted diseases (STDs), human immunodeficiency virus (HIV) infection, and tuberculosis; mental health; immunization; substance abuse; and three areas of prevention of special interest to DHHS-sexual assault, disabilities, and emergency medical services. This report focuses on measures that states and the federal government can use over the next 3 to 5 years to negotiate agreements and monitor performance in these areas. A later report will examine additional measures that might be developed from new research findings on program effectiveness or as improvements are made to state and federal surveys and data systems.

Facilitating Health Communication with Immigrant, Refugee, and Migrant Populations Through the Use of Health Literacy and Community Engagement Strategies: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The increasingly diverse ethnic composition of the United States population has created a profound and ongoing demographic shift, and public health and health care organizations face many challenges as they move to address and adapt to this change. To better understand how the public health and health care communities can meet the challenges of serving an increasingly diverse population, the Roundtable on Health Literacy conducted a public workshop on facilitating health communication with immigrant, refugee, and migrant populations through the use of health literate approaches. The goal of the workshop was to identify approaches that will enable organizations that serve these ethnically and culturally diverse populations in a manner that allows all members of these communities to obtain, process, and understand basic health information and the services needed to make appropriate health and personal decisions. This publication summarizes the presentations and discussions from the workshop.